Influence of sociodemographic factors on helicobacter pylori prevalence variability among schoolchildren in Leipzig, Germany. A long-term follow-up study - Bauer, Sophie; Krumbiegel, Peter; Richter, Matthias; Richter, Thomas; Röder, Stefan; Rolle-Kampczyk, Ulrike; Herbarth, Olf (Central European Journal of Public Health, 2011)
Background: Until the beginning of this decade the assumption was that the Helicobacter pylori prevalence increases with the age of the population under consideration. More and more epidemiological studies have been suggestive of constancy in Helicobacter pylori prevalence, but to date there has been no long-term follow-up study in a large group of children confirming this hypothesis. Methods: Following up our study of H. pylori among school starters and 2nd graders in 1998 and 2000, we conducted a third phase of this study in 2006 using the [13C]-Urea Breath Test and a detailed parent-completed epidemiological questionnaire to evaluate the development of prevalence among the overall population of 8th graders in the city of Leipzig (n=1,905), and especially of the subgroup of participants who took part in all three study phases (n=751). Results: The overall H. pylori prevalence was 6.5% and had not significantly changed since 1998 and 2000 (6.1%, 5.7% respectively). However, we noticed a significant lower prevalence in the subgroup that participated in all study phases (2.7%). Moreover, we observed a dependence of prevalence on distribution of sociodemographic risk factors such as foreign nationality of at least one parent, birth outside of Germany, low parental education and unemployment, and ?2 older siblings. Conclusion: The variability in prevalence is most likely a result of unequal sociodemographic family backgrounds.
Keywords: Helicobacter Infections; Helicobacter pylori; Follow-Up Studies; Prevalence; následné studie; Age Factors; Germany; Socioeconomic Factors; financování organizované; Německo; infekce vyvolané Helicobacter pylori; ženské pohlaví; prevalence; lidé; věkové faktory; socioekonomické faktory; mužské pohlaví; Financing, Organized; Humans; Female; Male